(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents our scientific perspectives on the phraseological idioms of the Uzbek language, which belongs to the Turkic language family, focusing on their linguistic features and linguo-cultural aspects. We will highlight their unique and distinctive characteristics by comparing them with other languages. Furthermore, the article will analyze the cultural aspects reflected in these phraseological expressions.